2012
DOI: 10.1177/0954008311433606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bisphenol-A ether diamine-based polyimide POSS nanocomposites for low K dielectric and flame-retardant applications

Abstract: Polyhedral oligomeric silsesquioxane (POSS) -polyimide (PI) hybrid nanocomposites were prepared by a two-step approach, bisphenol-A ether diamine (BAED) and pyromelletic dianhydride (PMDA) in 1-methyl-2-pyrrolidone (NMP) were used to prepare polyamic acid (PAA) to which varying weight percentages of OAPS in NMP were added. During the second step, the polycondensation was effected by thermal imidization. The formation of hybrid nanocomposites was confirmed by using FTIR spectra. The thermal properties of POSS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…The coefficient of thermal expansion was also decreased, while mechanical moduli and thermostability were also improved. The same POSS moiety was utilized later to crosslink pyromellitic anhydride -based PIs, with ether-linked cyclohexyl diamine [158] or bisphenol-A ether diamine [159], as well as a system prepared by BPTA and bis(4-amino-3,5-dimethylphenyl)-3-quinolylmethane [160]. It is confirmed that aminophenyl POSS is well dispersed in the matrices, improving mechanical properties and increasing T g .…”
Section: [Figure 22]mentioning
confidence: 64%
“…The coefficient of thermal expansion was also decreased, while mechanical moduli and thermostability were also improved. The same POSS moiety was utilized later to crosslink pyromellitic anhydride -based PIs, with ether-linked cyclohexyl diamine [158] or bisphenol-A ether diamine [159], as well as a system prepared by BPTA and bis(4-amino-3,5-dimethylphenyl)-3-quinolylmethane [160]. It is confirmed that aminophenyl POSS is well dispersed in the matrices, improving mechanical properties and increasing T g .…”
Section: [Figure 22]mentioning
confidence: 64%
“…Limiting oxygen indexes (LOI), which can indicate the flame retardancy of polybenzoxazine resins, were obtained from the char yield (CY) by Van Krevelen's equation (LOI = 17.5 + 0.4 * (CY)) . Normally, polymers with LOI values greater than 26 are considered to have self‐extinguishing properties.…”
Section: Resultsmentioning
confidence: 99%
“…There were various fillers, e.g. nanoscale graphene fluoroxide, graphene oxide, graphite‐like carbon nitride, KIT‐6, polyhedral oligomeric silsesquioxane, amino functionalized polyhedral oligomeric silsesquioxane, ladder‐poly(propylsilsesquioxane), nanosized silica, SBA‐15, pure silica zeolite nanocrystals and graphene oxide blended with octa(aminophenyl) silsesquioxane,…”
Section: Introductionmentioning
confidence: 99%